New evidence on teachers' working hours in England. An empirical analysis of four datasets. Issue 6 (2nd November 2021) - Allen, Rebecca; Benhenda, Asma; Jerrim, John; Sims, Sam
ABSTRACT: Surveys have revealed that teachers in England work far longer hours than their international counterparts, causing serious concern amongst both policymakers and the profession. Despite this, surprisingly little is known about the structure of and changes to teachers' working hours. We address this gap in the evidence base by analysing four different datasets. Working hours remain high: a quarter of teachers work more than 60 hours per week during term time, 40% report that they usually work in the evening and around 10% during the weekend. However, contrary to current narratives, we do not find evidence that average working hours have increased. Indeed, we find no notable change in total hours worked over the last twenty years, no notable change in the incidence of work during evenings and weekends over a fifteen year period and no notable change in time spent on specific tasks over the last five years. The results suggests that policy initiatives have so far failed to reduce teachers' working hours and that more radical action may need to be taken in order to fix this problem.